Implications of changing shipping patterns near communities across Arctic Canada - Alison Cook; Jackie Dawson; Jean Holloway; Michael Milton; Shirley Tagalik; Kukik Baker; Jimmy Muckpah; Shelly Elverum; Elizabeth Boyse; Melody S. Clark; Clara Manno; Vicky Peck; et al. (Regional Environmental Change, 2026)
The increase in shipping in the Canadian Arctic has significant impacts on Inuit coastal communities and their traditional way of life. Examples include the risk of chemical spills, underwater noise and ships’ hulls acting as vectors for non-indigenous species, all of which impact ecosystems and wildlife which Inuit rely on for health, food security and cultural sustainability. However, the number and types of ships travelling near communities and the associated risks remain poorly quantified, limiting effective management strategies. We use ship tracklines generated from Automatic Identification System (AIS) ship positions between 2013 and 2022 to calculate voyages within 20 km of 43 communities distributed throughout Northern Canada (north of 60° N and Hudson Bay). Over 10 years, voyages increased significantly by a factor of 1.7 (from 116 in 2013 to 317 in 2022), with the largest increases due to dry bulk, cargo and government/research vessels. This varies between communities, with 15 (35%) having shown little change or a small decrease in shipping, and 28 (65%) showing an increase. Six communities accounted for the majority of the overall increase. We examine these sites in detail, identifying drivers behind the voyage increases such as the proximity to mines, growing resupply needs, tourism expansion and increased navigability along transit routes close by due to the reduction in sea ice. Our results on the rate and drivers of change in ship traffic provide essential insights for local and regional governance of shipping impacts.

Expanding Monitoring Capacity for Potential Invasive Species in Arctic Canada With Environmental DNA Metabarcoding - Elizabeth Boyse; Melody S. Clark; Ian M. Carr; Alison J. Cook; Philippe Archambault; Jean E. Holloway; Zhewen Luo; Michael Milton; Mathieu Roy; Jackie Dawson; Victoria L. Peck (Global Change Biology, 2025)
To date, environmental conditions have been enough to act as an effective barrier to prevent non‐indigenous species from arriving and establishing in Arctic Canada. However, rapidly changing climatic conditions are creating more suitable habitats for non‐indigenous species to potentially establish and become invasive. Concurrently, shipping traffic in parts of Arctic Canada has increased by over 250% since 1990, providing an effective vector for transporting non‐indigenous species to the region. Arctic Canada has been historically undersampled, so Arctic biota inventories are incomplete, hampering efforts to establish if a species is new to the region (and potentially invasive) or newly discovered. In this study, we utilize environmental DNA (eDNA) metabarcoding and ships of opportunity to assess eukaryotic community composition and potential invasives along one of the busiest shipping routes, the Northwest Passage. One liter seawater samples were collected in triplicate at 27 locations, targeting touristic hotspots frequently visited by passenger vessels. Eukaryotic DNA was amplified from the 18S rRNA V9 and COI regions, resulting in 126 unique Amplicon Sequence Variants (ASVs) detected with COI and 391 ASVs with 18S, providing an important snapshot of current community composition. Copepods, dinoflagellates, and diatoms were the most abundant taxonomic groups, correlating well with previous net sampler surveys, validating the efficacy of eDNA for biodiversity surveillance. We also report the first detections of a prolific invasive species, the bay barnacle ( Amphibalanus improvisus ), in Arctic Canada. Further work is currently in progress to establish whether these detections represent transient barnacle larvae or sessile adults capable of recruiting and reproducing. Our study demonstrates the utility of eDNA for the detection of non‐indigenous species in a data‐poor area, which, if combined with citizen science initiatives and local communities, could provide a vital monitoring tool for the detection of new invasives in this rapidly changing area.

MLH1 c.27G>A (p.Arg9=) is a synonymous likely/pathogenic variant underlying variably mosaic constitutional MLH1 methylation in Lynch syndrome - Rocio Alvarez; Paula Climent-Cantó; GiWon Shin; Francesca Paola Aguirre; Lisa Zhou; Dennis J. Hazelett; Brent K. Larson; Covadonga Vara; Gabriel Capellá; Víctor Lorca Castellanos; Pilar Garre Rubio; Françoise Desseigne; et al. (Familial Cancer, 2025)

Community-identified risks to hunting, fishing, and gathering (harvesting) activities from increased marine shipping activity in Inuit Nunangat, Canada - Nicolien van Luijk; Natalie Ann Carter; Jackie Dawson; Colleen Parker; Kayla Grey; Jennifer Provencher; Alison Cook (Regional Environmental Change, 2022)
The rapid increase in marine shipping activity in Inuit Nunangat (i.e. in settled land claim regions of Arctic Canada), propelled by climate change and international interest in Arctic maritime trade, has heightened concerns among Inuit communities about the risks that more ships could pose for sustainable and subsistence hunting, fishing, and gathering (berries, plants, eggs, etc.) (referred to as harvesting in this article) activities considered vital for cultural well-being and local livelihoods. As part of the Arctic Corridors and Northern Voices project, ( www.arcticcorridors.ca ) a series of workshops, focus groups, and interviews were conducted in and with 14 communities across Inuit Nunangat that involved 133 marine experts and 59 youth community researchers. In this paper, we present the concerns identified by Inuit and local marine users about the risks of increased shipping activity specifically with respect to harvesting activities and then identify governance needs that could support sustainability. Results of the study are organised by three major risk themes: (1) Marine ecosystem contamination and degradation; (2) Disruption to harvesters’ travel and safety; and (3) Interference and disturbance of wildlife. All of these risks negatively impact harvesting activities in Inuit Nunangat. Considering the region is expected to be ice-free in summer by the end of the twenty-first century and that subsistence harvesting is crucial to the well-being of Inuit and northern communities, it is vital that research on this topic be conducted and then considered within ongoing Arctic governance and co-governance efforts.

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Amino acid transport by Sphingomonas sp. strain Ant 17 isolated from oil-contaminated Antarctic soil - Katherine Young; R. Brent Seale; Karen Olsson; Jackie Aislabie; Gregory M. Cook (Polar Biology, 2003)